The membranotropic activity of N-terminal peptides from the pore-forming proteins sticholysin I and II is modulated by hydrophobic and electrostatic interactions as well as lipid composition - Ros, Uris; Pedrera, Lohans; Diaz, Daylin; Karam, Juan C. de; Sudbrack, Tatiane P.; Valiente, Pedro A.; Martinez, Diana; Cilli, Eduardo Maffud [UNESP]; Pazos, Fabiola; Itri, Rosangela; Lanio, Maria E.; Schreier, Shirley; et al. (Indian Acad Sciences, 2011)
The sea anemone Stichodactyla helianthus produces two pore-forming proteins, sticholysins I and II (St I and St II). Despite their high identity (93%), these toxins exhibit differences in hemolytic activity that can be related to those found in their N-terminal. To clarify the contribution of the N-terminal amino acid residues to the activity of the toxins, we synthesized peptides spanning residues 1-31 of St I (StI(1-31)) or 1-30 of St II (StIl(1-30)) and demonstrated that StII(1-3.0) promotes erythrocyte lysis to a higher extent than StI(1-31). For a better understanding of the molecular mechanism underlying the peptide activity, here we studied their binding to lipid monolayers and pemeabilizing activity in liposomes. For this, we examined the effect on peptide membranotropic activity of including phospatidic acid and cholesterol in a lipid mixture of phosphatidylcholine and sphingomyelin. The results suggest the importance of continuity of the 1-10 hydrophobic sequence in StIl(1-30) for displaying higher binding and activity, in spite of both peptides' abilities to form pores in giant unilamellar vesicles. Thus, the different peptide membranotropic action is explained in terms of the differences in hydrophobic and electrostatic peptide properties as well as the enhancing role of membrane inhomogeneities.
Keywords: Actinoporin; hemolytic peptide; permeabilizing activity; pore-forming toxin; sticholysin